Study of magnetic entropy and heat capacity in ferrimagnetic Fe3Se4 nanorods - Sen Bishwas, Mousumi; Poddar, Pankaj (Journal Of Physics D-Applied Physics, 2016)
Change in the magnetic entropy and specific heat capacity in Fe3Se4 nanorods synthesized by a wet-chemical method in a broad temperature (215-340 K) and magnetic field range (0-60 k Oe) was studied. The isothermal magnetic entropy change (Delta S-M) is estimated by an indirect method from the isothermal magnetization curves measured in this temperature range. S-M(max) of -46 x 10(-2) J kg(-1).K-1 was obtained at similar to 317 K when the field was changed from 0 to 60 kOe. The maximum in the isothermal magnetic entropy change (Delta S-M) is observed in close proximity to TC (similar to 323 K), which is linked to the order-disorder transition. The nature of this transition was analyzed by universal curve behavior. The temperature and magnetic field dependence of specific heat capacity was studied and analyzed to estimate the adiabatic temperature change (Delta T-ad). The magnetic entropy change of Fe3Se4 nanoparticles is found to be comparable with similar ferrite and manganite nanoparticle systems and a broad operating temperature window of similar to 30 K was observed around room temperature.
Keywords: heat capacity; iron selenide; Magnetic anisotropy; magnetic entropy; order-disorder phase transition